Women's knowledge about the preventive examination for cervical cancer vv (Research, Society and Development, 2021)
Cervical cancer is a public health problem due to its high incidence in the country, in this context there is the preventive examination for cervical cancer (PCCU), which is essential for the early diagnosis of the disease. Thus, this study aims to identify the knowledge of women in the countryside of Tocantins, about the importance of performing the preventive examination for cervical cancer. This is a cross-sectional field research, with qualitative and quantitative analysis, carried out with women assisted by the Health Education Clinic (CEPS) of the Santa Catarina Educational Institute - Faculdade Guaraí (IESC-FAG), in Guaraí – Tocantins. The study points out that the participants have regular knowledge about the PCCU exam where 100% (30) recognize and understand the importance of taking the exam and 96.7 (29) its purpose. Thus, nursing must pay increasing attention to the opportunity to clarify doubts at the time of consultation, providing an excellent listening that, in addition to the technical performance of the examination, encompasses all its aspects, bringing even more knowledge to women, as that this is a fundamental factor for adherence to the exam, thus being possible to reduce the incidence of the studied pathology.